The Energy Efficiency Awareness for Selangor Office Buildings - Abd Rahman, Anarohana; Tami, Hannifah (Recent Trends in Civil Engineering and Built Environment, 2025)
The imperative adoption of Energy Efficiency (EE) is underscored, particularly in developing nations like Malaysia. With the building sectors consuming a substantial 40% of the world’s energy, 12% of water, and contributing 40% of landfill waste, addressing energy efficiency in this domain is paramount. This study focuses on identifying the energy efficiency practices in office buildings based on the Green Building Index (GBI) and analyzing the awareness levels among occupants in Selangor. The survey, employing questionnaires and semi-structured interviews, targeted occupants in three office buildings. The sample size was S=168, covering demographics, energy efficiency practices, and awareness levels. Data analysis, conducted using Statistical Package for Social Science (SPSS) version 27, included descriptive analysis and mean score methods. Results indicated widespread agreement among occupants regarding the implementation of energy efficiency practices and their awareness of such initiatives in office buildings. Nevertheless, a comprehensive assessment under GBI criteria is recommended for future research to gauge the effectiveness of energy efficiency practices in existing office buildings.